Allah Sebagai Bapa dan Ibu: Studi Komparatif Dari Konstruksi Allah sebagai Bapa dalam Injil Matius dan Allah sebagai Ibu dalam Teologi Feminis - Pelita Hati Surbakti (The New Perspective in Theology and Religious Studies, 2020)
Because it is considered as a product of androcentric culture that can bring up misogynists, some feminist Christian theologians reject the hegemony of the use of the word "Father" as a calling for God. They considered that Mother was also worthy, even should be prioritized, to call God. Unfortunately this proposal seems to have been born from a less positive interpretation of the word Father in the Bible. Through this article, I prove that the title Father for God in the Gospel of Matthew does not contain the misogynistic nuances. On the contrary, through comparative studies, the construction of the proper theology of Matthew's gospel and feminist theology is actually based on the same socio-religious background that is fighting against proper theology which proclaims a transcendent and hierarchical portrait of God. Both emphasize an immanent God. With this similarity, God as Mother should not be the antithesis of God as Father, but both are complementary.